2012
DOI: 10.1007/s11434-012-5366-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of five heavy metals at sub-lethal concentrations on the growth and photosynthesis of Chlorella vulgaris

Abstract: The impact of sub-lethal concentrations (0.05, 0.5, 5 μmol L −1 ) of the heavy metals copper (Cu), chromium (Cr), zinc (Zn), cadmium (Cd) and lead (Pb) on the growth and photosynthesis of Chlorella vulgaris was studied during 96 h exposure experiments. The results showed that the effects of these five metals on the growth of Chlorella vulgaris were dependent on both concentration and exposure time. It was found that 5 μmol L −1 treatments of Cu, Cr, Zn, Cd and Pb significantly inhibited the growth of Chlorella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 18 publications
5
46
0
1
Order By: Relevance
“…Cu may also impair the PSII electron transport on its reducing side by affecting the rate of oxidoreduction [148]. The inhibitory effect of copper on the photosynthetic apparatus of several species of algae has been examined, including E. gracilis [149,150], S. quadricauda [141], S. obliquus [151], S. incrassatulus [152], C. pyrenoidosa [153], C. vulgaris [154], Planothidium lanceolatum and Isochrysis galbana [155], D. tertiolecta, Promocentrum minimum, Synechococcus sp., and Thalassiosira weissflogii [145].…”
Section: Juarez Et Al (2008) [158]mentioning
confidence: 99%
See 2 more Smart Citations
“…Cu may also impair the PSII electron transport on its reducing side by affecting the rate of oxidoreduction [148]. The inhibitory effect of copper on the photosynthetic apparatus of several species of algae has been examined, including E. gracilis [149,150], S. quadricauda [141], S. obliquus [151], S. incrassatulus [152], C. pyrenoidosa [153], C. vulgaris [154], Planothidium lanceolatum and Isochrysis galbana [155], D. tertiolecta, Promocentrum minimum, Synechococcus sp., and Thalassiosira weissflogii [145].…”
Section: Juarez Et Al (2008) [158]mentioning
confidence: 99%
“…Stimulatory effects on algal photosynthesis at low exposure concentrations of Zn 2+ have been observed. For example, C. vulgaris after 96 h of exposure at treatment concentration of 5 μmol L −1 showed that the proportion of the maximum quantum yield of PSII promoted by Zn was approximately 10% [154]. However, when the external concentration of Zn 2+ is beyond a limited value, it causes harmful effects; hence, its concentration in the cells must be controlled.…”
Section: Juarez Et Al (2008) [158]mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, compared with Ni, Pb showed a higher toxicity. However, Ouyang et al (2012) investigated and compared the effects of several heavy metals on chlorella toxicity, and the results showed that Pb did not cause any effect on Chlorella vulgaris. The reasons for this may be that the Microcystis flos-aquae used in the present study was the prokaryotic cyanobacteria, and the algae Chlorella vulgaris was eukaryotic algae.…”
Section: Adsorption Capacity Of Algicide To Heavy Metalsmentioning
confidence: 99%
“…At sub-lethal concentrations, Ouyang et al discovered that the addition of Cu at 5 μmol/L in algae culture vastly inhibited the growth of Chlorella, and similar inhibitory phenomenon were also observed in the same concentration for Cr [5]. Nevertheless, compared with other heavy metals such as Cd, Cu, As, and Sb, Pb with a higher IC 50 to Chlorococcum seems to be less hazardous in aquatic systems [6].…”
mentioning
confidence: 93%